Adaptive management, international co-operation and planning for marine conservation hotspots in a changing climate. (March 2015) - Gormley, Kate S.G.; Hull, Angela D.; Porter, Joanne S.; Bell, Michael C.; Sanderson, William G.
Abstract: The aim of this study is to predict changes in the distribution and extent of habitat forming species defined as "Priority Marine Habitats" (PMHs) in the North-East (NE) Atlantic under future scenarios of climate-induced environmental change. A Species Distribution Modelling method was used for each PMH to map the potential distribution of "most suitable" habitat. The area and percentage cover was calculated within each country׳s Exclusive Economic Zone for the baseline (2009) and the projected (2100) years. In addition, a conservation management score was calculated based on the number of PMHs that co-occur in assessment units. Overall, this study reveals the potential for movement and/or change in the extent of some PMHs across the NE Atlantic under an increased ocean temperature scenario (4 °C) by 2100. There are regional differences in the predicted changes and some countries will experience greater/different changes than others. The movement of biodiversity hotspots (where one or more PMHs occur in the same broad area) provides both opportunities and risks for conservation management that are discussed. Co-operation between neighbouring countries and marine regions will require substantial enhancement in order to provide a robust adaptive management strategy going forward.